Late HIV testing in a cohort of HIV-infected patients followed in Puerto Rico - Tossas-Milligan, Katherine Y. (P R Health Sci J, 2015)
OBJECTIVE: Late HIV testing (LT) defined as an AIDS diagnosis within a year of first positive HIV test is associated with higher HIV transmission, lower HAART effectiveness, and worse outcomes. Latinos represent 36% of LT in the US, yet research concerning LT among HIV cases in Puerto Rico is scarce. METHODS: Multivariable logistic regression analysis was used to identify factors associated with LT and Cochran-Armitage test to describe LT trends in an HIV infected cohort followed at a specialized HIV clinic in Puerto Rico. RESULTS: From 2000 to 2011, 47% of eligible patients were LT, with lower median CD4 count (54 vs. 420 cells/mm3) and higher median HIV viral load counts (253,680 vs. 23,700 copies/mL), when compared to non-LT patients. LT prevalence decreased significantly, from 47% in 2000 to 37% in 2011. In a mutually adjusted logistic regression model, males, older age at enrolment and past history of IDU significantly increased LT odds whereas history of amphetamine use decreased LT odds. Stratified by mode of transmission, only men who have sex with men (MSM), had a significant reduction in the proportion of LT, from 67% in 2000 to 33% in 2011. CONCLUSION: These results suggest a gap in early HIV detection in Puerto Rico that decreased only among MSM. A closer evaluation of HIV testing guideline implementation among non MSM in the Island is needed.